The Role Of Using Queuing Theory In Making Administrative Decisions A Case Study Of The Orthopedic Clinic In Tishreen University Hospital – Lattakia - الشيخ حسن, فداء; السليمان, نسرين (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study aimed to demonstrate the role of using waiting queue models in administrative decision-making, in order to solve the problem of waiting in the orthopedic clinic at Tishreen University Hospital. To achieve this goal, a waiting queue model was formulated and resolved using (QM Windows) Where this study was applied in the orthopedic clinic at Tishreen University Hospital in Lattakia during the period from 1/8/2021 to 15/9/2021. The study found an alternative model to solve the waiting problem in the orthopedic clinic, as the alternative model contributed to determining the ideal number of service centers that reduces waiting time and reduces the number of patients in the waiting queue to the least possible number.